Disruptive technologies, climate change and shipping - Soyer, Barış; Tettenborn, Andrew (informa law from Routledge, 2022)
"This book analyses the impact of two vital and contemporary developments on shipping law and practice: disruptive technologies and climate change. It considers the impact of these new technologies, honing in on likely emerging issues and unresolved questions, especially about existing and potential private law liabilities and concentrates, from the point of view of English, EU and international law, on the legal implications of climate change and associated environmental risks in the shipping sector. Written by a contributor team drawn from the most experienced and knowledgeable academics and practitioners in shipping law, this treatment of these growing areas of practice will be of great use to lawyers and administrators across the world"--
Keywords: Maritime law; Technological innovations / Law and legislation; Climatic changes / Law and legislation; Maritime law / Environmental aspects